Nicaragua : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2006)
This Selected Issues paper for Nicaragua reports that the Central America-Dominican Republic-United States Free Trade Agreement (CAFTA-DR) provides a general framework for country-specific bilateral agreements. In addition to the phased liberalization of trade in goods, CAFTA-DR provides broad market access for services and includes provisions in areas such as intellectual property rights, investment, government procurement, and competition policies. Labor provisions are slightly tighter than under other similar agreements by offering a platform to examine the quality of existing legislation, rather than only ensuring its implementation.